SCHOOLBOYS’ CONSCIENTIZATION ON ONLINE PORNOGRAPHY THROUGH DISCUSSION AND REFLECTION - Ruškus, Jonas; Sujeta, Irmantas (Acta Paedagogica Vilnensia, 2011)
Online pornography is considered as one form of violence and victimization. Schoolboys often are users of online pornography and, at the same time, they become objects of violence and victimization. Online pornography is one of the themes which is suppressed in formal education settings, because it is of immoral and illegitimate character. The article presents results of participatory action research implemented at the secondary school. The typical sampling was organized, 13 schoolboys of age 16–17 participated in three focus groups. After watching B. Goldthwait’s film World’s Greatest Dad where the film hero a schoolboy deals with a pornography theme, research participants discussed and reflected their own experience, and also perceived threats of online pornography. Research participants discussed and designed measures for education and prevention for coping with online pornography. As the use of online pornography is an important part of informal education with threatening consequences, the formal education should turn to this issue creating space and time for dialogue and reflection. The implemented participatory action research process and results revealed that dialogue promotes the expression and hearing of different emotions and experiences, the reflection on the possible victimization consequences, the development of a broader view and deeper understanding of the phenomena of online pornography.